Development of a protocol to phenotype sweet cherry (Prunus avium L.) for resistance to bacterial canker. (October 2018) - Mgbechi-Ezeri, Josephine U.; Johnson, Kenneth B.; Porter, Lyndon D.; Oraguzie, Nnadozie C.
Abstract: Suppression of bacterial canker disease of sweet cherry caused by Pseudomonas syringae pv. syringae (Pss), utilizing resistant scion and rootstock varieties holds promise as a cost-effective management strategy. However, a reproducible and rapid method for screening large breeding populations for resistance to Pss poses a challenge. Sweet cherry cultivars Bing, Sweetheart, Regina, Moreau, Emperor Francis and Rainier were used to examine the effects of Pss isolate, inoculum concentration (1 × 10 2 to 1 × 10 8 cfu/ml), leaf age (collected from the tip, middle or base of the shoot) and inoculation assay method (attached versus detached leaf) on disease development. Disease severity was influenced significantly ( P ≤ 0.05) by inoculum concentration and the virulence of the Pss isolate. An inoculum concentration of 1 × 10 8 cfu/ml provided the best disease response in both leaf assays and is recommended for disease screening. Also, a significant Pss isolate x cultivar effect was observed suggesting that proper selection of Pss isolate for disease screening is critical. Disease severity was significantly ( P ≤ 0.05) greater for newly expanding leaves in detached assays than for leaves classified as young or old. Disease response among cultivars for attached and detached leaf assays was significantly correlated (r = 0.53, P = 0.002), but the detached leaf assay provided better separation in disease severity among cultivars. We conclude that the genotypic variation in disease response among sweet cherry germplasm can be differentiated based on a detached assay using new leaves, a highly virulent Pss isolate, and an inoculum concentration of 1 × 10 8 cfu/ml. Highlights: Pathogen virulence had a significant effect ( P ≤ 0.05) on cultivar susceptibility to bacterial canker disease. Disease response among sweet cultivars in detached and attached assays was significantly correlated (r = 0.53, P < 0.05). Host disease response using the detached leaf assay correlated with known field disease resistance of cultivars. Disease response was influenced ( P ≤ 0.05) by assay method and inoculum concentration. Bacterial canker disease severity on sweet cherry cultivars decreased with increasing leaf maturity.